2016
DOI: 10.3390/su8090933
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cropland Status and Their Driving Factors in the Koshi River Basin of the Central Himalayas, Nepal

Abstract: Abstract:In recent decades, human activities have significantly transformed land use and land cover (LULC) and the environment of the Central Himalayas region. LULC is a major component of environmental and climatic research. The aim of this study was to determine the changes in cropland status and its drivers in the Koshi River Basin (KRB) of the Central Himalayas region of Nepal between 1978 and 2010. The cropland status in 1978 was obtained from the Land Resources Mapping Project (LRMP) datasets. The cropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 39 publications
5
54
1
Order By: Relevance
“…Clearly, beyond localized urban-growth management and land-use zonation in Tarai, the prevention of agricultural loss due to urban growth in Tarai will require national development programmes focused on Nepal's poorer regions to entice would-be economic migrants to remain. Previous studies [29,[34][35][36]59,68] have similarly reported the loss of highly fertile agricultural lands in the different part of Nepal due to urbanization and population pressure, suggesting that our regional observations capture a general trend that is likely to continue, and even intensify, in the absence of any intervention to the contrary.…”
Section: Discussionsupporting
confidence: 56%
“…Clearly, beyond localized urban-growth management and land-use zonation in Tarai, the prevention of agricultural loss due to urban growth in Tarai will require national development programmes focused on Nepal's poorer regions to entice would-be economic migrants to remain. Previous studies [29,[34][35][36]59,68] have similarly reported the loss of highly fertile agricultural lands in the different part of Nepal due to urbanization and population pressure, suggesting that our regional observations capture a general trend that is likely to continue, and even intensify, in the absence of any intervention to the contrary.…”
Section: Discussionsupporting
confidence: 56%
“…[12]. However, our study on Dudh Koshi did not showed the slight reduction in crop farming during 2010 described for the larger Koshi River Basin [12]. Nevertheless, since our study area focuses on the mountain environment, our outcomes seems to confirm the conclusion of another recent study (2016) that "agriculture practices and patterns that were once intensely distributed in lowland areas have spread to higher altitudes" [13].…”
Section: Resultssupporting
confidence: 75%
“…To handle the different spatial detail of source data and to smooth any local error in the crop maps, all the parameters were rescaled to a spatial resolution of 250 m prior the regression analysis. [12]. However, our study on Dudh Koshi did not showed the slight reduction in crop farming during 2010 described for the larger Koshi River Basin [12].…”
Section: Resultscontrasting
confidence: 67%
“…A total of 901, 905 and 890 stratified random points were generated in the classified image of 2000, 2010 and 2017, respectively, and were verified in Google Earth imageries. The topographical maps during 1992-2001 from the Survey Department, Government of Nepal were also used for data verification [29,59,61].…”
Section: Accuracy Assessmentmentioning
confidence: 99%